Autoria Interdisciplinar: o reconhecimento do professor da educação básica como intelectual do ensino e a emancipação dos alunos - Dias, Dorotéa Bittencourt (2019)
This is a study is for analyze role of researchers teacher in the city of São Paulo, considering the interdisciplinary cycle (4,5 and 6 grade) needs in the town of São Paulo, that assumes that the interdisciplinary is the way for authorship and leadership. According to the program “Mais Educação São Paulo” this cycles of learning operates in a priority but not exclusive way, the issue of the authorship by learning from curricular projects committed with a social intervention. Consider that the authorship process have consequences in the learning process, claim for a skilled researcher teacher. We believe that the formation of a researcher is a skill that is part of our teaching work, but sometimes is not considerate in the basic education. The orientation of a authorship work requires from the teacher an engagement and also from the research formation. That requirement set a challenge, because the formulation of the research skill is not considered one requirement to the magisterium practice in the Brazilian basic education. This research goal is to present the authorship as a effective resource to reach to equality and the continuity of everyone in a Brazilian public school, also to show that the work with interdisciplinary cycles project’s help teachers and students to became writers in this process. In this way we will analyze the importance of the interdisciplinary authorship of the basic education teacher, as a instrument of the assurance of the learning right, considering the interdisciplinary point of view we choose one of the projects developed on the interdisciplinary cycle for the illustration of the interdisciplinary authorship as the key to overcome the dichotomy learn-research, show that the research is the learning process key